Linking Ethanol-Addictive Behaviors With Brain Catecholamines: Release Pattern Matters - Grinevich, Vladimir P.; Krupitsky, Evgeny M.; Gainetdinov, Raul R.; Budygin, Evgeny A. (Frontiers in Behavioral Neuroscience, 2021)
Using a variety of animal models that simulate key features of the alcohol use disorder (AUD), remarkable progress has been made in identifying neurochemical targets that may contribute to the development of alcohol addiction. In this search, the dopamine (DA) and norepinephrine (NE) systems have been long thought to play a leading role in comparison with other brain systems. However, just recent development and application of optogenetic approaches into the alcohol research field provided opportunity to identify neuronal circuits and specific patterns of neurotransmission that govern the key components of ethanol-addictive behaviors. This critical review summarizes earlier findings, which initially disclosed catecholamine substrates of ethanol actions in the brain and shows how the latest methodologies help us to reveal the significance of DA and NE release changes.. Specifically, we focused on recent optogenetic investigations aimed to reveal cause-effect relationships between ethanol-drinking (seeking and taking) behaviors and catecholamine dynamics in distinct brain pathways. These studies gain the knowledge that is needed for the better understanding addiction mechanisms and, therefore, for development of more effective AUD treatments. Based on the reviewed findings, new messages for researches were indicated, which may have broad applications beyond the field of alcohol addiction.